Evaluating the Cardiovascular Impact of Rheumatoid Arthritis through Clinical Disease Activity Index Scores: A Cross-sectional Study at a Rural Teaching Hospital - Keyur Saboo; Sunil Kumar; Sourya Acharya; Rajesh Sarode; Rinkle Gemnani; Avinash Parepalli (Journal of the Practice of Cardiovascular Sciences)
Introduction:Rheumatoid arthritis (RA) is associated with an increased risk of cardiovascular diseases, leading to higher morbidity and mortality rates compared to the general population. The Clinical Disease Activity Index (CDAI) is a validated composite index used to assess disease activity in patients with RA, which may guide therapeutic decisions and help monitor disease progression or response to treatment. This study highlights about cardiovascular evaluations at all stages of rheumatoid disease activity as per CDAI.